ANALISIS PENERAPAN SISTEM AKUNTANSI PENERIMAAN PAJAK HOTEL DI DPPK KOTA SURABAYA - Aprilia, Annisa Ayu; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out and to analyze the implementation of hotel tax revenue accounting system in the Dinas Pendapatan dan Pengelolaan Keuangan Kota Surabaya. This research is a qualitative descriptive research. The data collection technique is based on the observation at the office of Dinas Pendapatan dan Pengelolaan (DPPK) Kota Surabaya, by conducting interview also the documentation. The hotel tax revenue accounting system consists of procedures i.e. revenue, records and documents at the Dinas Pendapatan dan Pengelolaan (DPPK) Kota Surabaya has already been performed properly and it is compatible with the accrual based Government Accounting Standards which is based on the Government Regulations No. 71 of 2010. The problems that have to be dealt with are the limited human resources and the lack of comprehension of officers in the implementation of accrual based accounting system and inadequate technology. Therefore, it has been expected to provide training and learning periodically and comprehensively to the human resources so they will be more professional in the implementation of the accounting system.Keywords: The Hotel Tax Revenue Accounting System, The Accrual Based Government Accounting Standards, Local Tax